Surgery for Patients With Recalcitrant Plantar Fasciitis: Good Results at Short-, Medium-, and Long-term Follow-up. Issue 3 (20th March 2014) - Wheeler, Patrick; Boyd, Kevin; Shipton, Mary
Background: Plantar fasciitis is a common cause of foot pain, and although many episodes are self-limiting with short duration, 10% leave chronic symptoms. Recalcitrant cases can be managed surgically, with studies demonstrating good results in the short term but uncertainties over longer term outcomes. Purpose: To assess the outcome following surgical intervention for patients with plantar fasciitis. Study Design: Case series; Level of evidence, 4. Methods: Seventy-nine patients were identified from operative diaries undergoing plantar fasciotomy surgery between 1993 and 2009. They were contacted to investigate long-term results using self-reported outcome measures. Results: Sixty-eight responses were received (86% response rate), with an average of 7 years (range, 1-15 years) of follow-up. Patients reported an average reduction in pain by visual analog scale of 79%, and 84% of patients were happy with the surgical results. Greater success was achieved in patients with shorter duration of symptoms preoperatively. No deterioration in success was seen over time. Conclusion: Plantar fasciotomy surgery for plantar fasciitis remains controversial, with biomechanical arguments against surgery; however, this article reports good success following surgery over a long follow-up period. The results of current operative techniques need to be fully investigated for longer term success, as do the outcomes of newer nonoperative management strategies.